How Zakat Responds to the Global Recession? An Implementation From Indonesia’s National Zakat Regency (BAZNAS) - Fitriani, Aprilya (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2023)
The global recession is an economic phenomenon that can have a significant negative impact on various sectors of life, especially for more vulnerable people. In this context, this study aims to examine the role of Zakat in overcoming the impact of the global recession. Research Methods: This study uses a literature review approach by analyzing related documents. The data obtained is analyzed thematically to identify various mechanisms and strategies that can be used by Zakat in overcoming the impact of the global recession. Finding/Results: The results of the study show that zakat has great potential in making a significant contribution to overcoming the impact of the global recession. The role of zakat can be seen from several aspects, including Redistribution of Wealth, Economic Empowerment, and Improved Social Welfare. Conclusion: The findings of this study indicate that zakat can play a role in minimizing the impact of the global recession. This study is limited to the portrait of zakat management by the government, which is reflected in innovative zakat utilization programs but has not looked specifically at the direct benefits of zakat in improving the standard of living of the economy, one of which is through saving activities. In line with this, further research is needed on the integration of zakat in increasing economic activity and investment.